Effectiveness of fire safety implementation in heritage buldings / Nurin Ezzati Mohd Fadzil and Mohd Azian Zaidi - Mohd Fadzil, Nurin Ezzati; Zaidi, Mohd Azian (2023)
This study investigates the implementation of fire safety in heritage buildings. It describes the contributory factors to the lack of fire safety implementation in historic buildings. A quantitative method has been selected to aid in identifying the factors, namely by obtaining responses to a survey questionnaire. In the literature review phase, seven factors were identified as initial contributors to the lack of fire safety implementation in heritage buildings. These factors were the low level of fire safety management systems, methods used to improve fire safety in historic buildings, fire safety systems, cost, fire safety awareness, facilities manager factors, and fire safety implementation. Eight variables were identified and tested using a survey questionnaire. These variables were maintenance of the fire protection system, cost-effective consumption, installation of fire-fighting system type, standard of management, housekeeping and maintenance, fire risk, method to improve fire safety, understanding about fire safety, and knowledge about fire hazards in historic buildings. The results of the analysis found that one factor recorded a mean value below 3.50, indicating that the factor is not statistically significant, thus only seven factors were identified as crucial for improving the implementation of fire safety in historic buildings when the mean value was greater than 3.50.